Analisis Hubungan Perlindungan Privasi dan Keamanan Terhadap Loyalitas Nasabah Bank Nagari Pada Penggunaan QRIS di Kota Padang - Rahma Yani; Alima Shofia; Trinda Farhan Satria (JUEB : Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the relationship between privacy protection and security on customer loyalty of Bank Nagari in using the Quick Response Code Indonesian Standard (QRIS) in Padang City. The research background is based on increasing cyber threats such as phishing and ransomware, which raise concerns about the security of customers’ personal data. The research employed a quantitative method with multiple correlation techniques using 307 respondents obtained through incidental sampling. The results show a positive relationship between privacy protection and security with customer loyalty, with a multiple correlation value of 0.534 and a determination coefficient of 0.285. This means that 28.5% of customer loyalty is influenced by both variables. Bank Nagari is advised to strengthen its privacy protection and security strategies to enhance customer trust and loyalty.